PENERAPAN STRATEGI PEMBELAJARAN COOPERATIVE TYPE SYNERGETIC TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 013 PAGARAN TAPAH DARUSSALAM - Naiborhu, Rusmawati (Aksara Public, 2017)
This research is motivated by the poor results of social studies class V students of SD Negeri 013 Pagaran Tapah Darussalam. This study aims to determine whether the application of cooperative learning strategies Teaching Type Synergetic can improve learning outcomes IPS fifth grade students of SD Negeri 013 Pagaran Tapah Darussalam, held for 1 month. As the subjects in this study were students of class V 2014-2015 school year the number of students as many as 20 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the results of the study as described in chapter IV can be concluded that the application of cooperative learning strategies Teaching Type Synergetic can improve learning outcomes IPS fifth grade students of SD Negeri 013 Pagaran Tapah Darussalam. The successful implementation of cooperative learning strategies Type Synergetic Teaching in social studies, it is known that the learning outcome of the first cycle to the second cycle. In the first cycle shows that the learning outcomes of students is still relatively low with an average percentage of 69.00%. While the results of the test in Cycle II students' learning outcomes achieved an average 82.50% which is very high. Based on these data, it is known that an increase in student learning outcomes from scoring 69.00%. be 82.50% which is influenced by the teacher's activities are further enhanced, particularly in terms of presenting the material and provide motivation to the students for learning.